Patterns and Correlates of Contacting Clergy for Mental Disorders in the United States - Wang, Philip S (Blackwell Science Inc, 2003)
OBJECTIVE: To present nationally representative data on the part played by clergy in providing treatment to people with mental disorders in the United States. DATA SOURCES: The National Comorbidity Survey (NCS), a nationally representative general population survey of 8,098 respondents ages 15–54. STUDY DESIGN: Cross-sectional survey DATA COLLECTION: A modified version of the Composite International Diagnostic Interview was used to assess DSM-III-R mental disorders. Reports were obtained on age of onset of disorders, age of first seeking treatment, and treatment in the 12 months before interview with each of six types of professionals (clergy, general medical physicians, psychiatrists, other mental health specialists, human services providers, and alternative treatment providers). PRINCIPAL FINDINGS: One-quarter of those who ever sought treatment for mental disorders did so from a clergy member. Although there has been a decline in this proportion between the 1950s (31.3 percent) and the early 1990s (23.5 percent), the clergy continue to be contacted by higher proportions than psychiatrists (16.7 percent) or general medical doctors (16.7 percent). Nearly one-quarter of those seeking help from clergy in a given year have the most seriously impairing mental disorders. The majority of these people are seen exclusively by the clergy, and not by a physician or mental health professional. CONCLUSIONS: The clergy continue to play a crucial role in the U.S. mental health care delivery system. However, interventions appear to be needed to ensure that clergy members recognize the presence and severity of disorders, deliver therapies of sufficient intensity and quality, and collaborate appropriately with health care professionals.